Meta Analisis:Sifat Mengikuti Kata Hati dan Kinerja dalam Penjelasan Sufisme - Nurus Sa'adah (Jurnal Sosiologi Agama, 2015)
This article examined the relationship between conscientiousness and job performance. The author used Sufism perspective to explained the dynamic on research findings of this metaanalytic. The meta-analytic consisted of 48 studiesfrom 20 articles. Summary analysis provided support for the hypothesis that conscientiousness had a correlation on job performance. The result indicated that conscientiousness positively influenced people’s job performance.Keywords: Conscientiousness, Job Performance, Sufism